2020
DOI: 10.26719/emhj.20.056
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in the distribution of Sudan’s health resources

Abstract: Background: Equal distribution of health resources has been a core objective of both long-and medium-term strategic plans for the health sector in Sudan. However, the targets of these plans have not yet been achieved, resulting in weak performance of the whole health system. The unequal distribution of the health resources has resulted in significant regional disparities in provision of health care services. Aims: This study aims to describe and analyse the inequality in geographic distribution of public secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…People who have tested for cholesterol and/or received health care advice are more likely to use health services and, consequently, may reduce the odds of undiagnosed HTN [ 16 ]. Rural residents in Sudan may have poorer access to health care services than urban residents, hindering them from screening of blood pressure [ 30 ]. Contrary to several previous studies [ 5 , 7 , 13 - 15 ], we did not find an association between socioeconomic status (education) with undiagnosed HTN.…”
Section: Discussionmentioning
confidence: 99%
“…People who have tested for cholesterol and/or received health care advice are more likely to use health services and, consequently, may reduce the odds of undiagnosed HTN [ 16 ]. Rural residents in Sudan may have poorer access to health care services than urban residents, hindering them from screening of blood pressure [ 30 ]. Contrary to several previous studies [ 5 , 7 , 13 - 15 ], we did not find an association between socioeconomic status (education) with undiagnosed HTN.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization points out that equity in health services means that members of society should have demand-oriented access to health services, rather than depending on factors such as ethnicity, social status, income level, and religious beliefs [ 3 ]. However, inequitable allocation of health resources is currently a global problem, especially in developing countries [ 4 ]. In the 2030 Agenda for Sustainable Development, the United Nations has clearly identified "ensuring universal access to health and health care services and achieving universal health coverage" as the main goal.…”
Section: Introductionmentioning
confidence: 99%
“…This paper, in line with Shinjo [ 96 ] and Paramita [ 97 ], finds that interregional differences in medical resources in China, Japan, and Indonesia are small, and the Gini indices of hospitals, doctors, and beds are generally less than 0.4, indicating the achievement of spatially balanced development. In contrast, other scholars found that the intercontinental distribution of health resources is extremely unequal in Ethiopia, Mongolia, Iran, and Sudan [ 98 ]. For example, Woldemichael [ 99 ], Chavehpour [ 100 ], and Rezaei [ 101 ] found that the Gini index of medical resources in Ethiopia and Iran is generally greater than 0.4, and even up to 0.75; further, Erdenee [ 102 ] found that the Gini indices of doctors and beds in Mongolia were 0.74 and 0.69, respectively.…”
Section: Discussionmentioning
confidence: 95%